2011
DOI: 10.3389/fncel.2011.00004
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Molecular Diversity of GABAergic Synapses

Abstract: GABAergic synapses exhibit a high degree of subcellular and molecular specialization, which contrasts with their apparent simplicity in ultrastructural appearance. Indeed, when observed in the electron microscope, GABAergic synapses fit in the symmetric, or Gray’s type II category, being characterized by a relatively simple postsynaptic specialization. The inhibitory postsynaptic density cannot be readily isolated, and progress in understanding its molecular composition has lagged behind that of excitatory syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 170 publications
(229 reference statements)
0
27
0
Order By: Relevance
“…GABAergic synapses exhibit an extraordinary diversity in terms of molecular, anatomic and physiological properties (Cherubini and Conti, 2001; Klausberger and Somogyi, 2008; Kubota et al, 2016; Sassoe-Pognetto et al, 2011). In hippocampus, principal neurons are innervated by over twenty distinct types of interneurons (Klausberger and Somogyi, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GABAergic synapses exhibit an extraordinary diversity in terms of molecular, anatomic and physiological properties (Cherubini and Conti, 2001; Klausberger and Somogyi, 2008; Kubota et al, 2016; Sassoe-Pognetto et al, 2011). In hippocampus, principal neurons are innervated by over twenty distinct types of interneurons (Klausberger and Somogyi, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…As GABAergic inhibition is important in almost every aspect of brain physiology and the dysregulation of GABAergic synapse development has been implicated in many neurological and neuropsychiatric disorders (Ko et al, 2015; Ramamoorthi and Lin, 2011), it is critical to understand the molecular determinants of GABAergic synapse formation. Interestingly, GABAergic synapses exhibit remarkable diversity (Cherubini and Conti, 2001; Sassoe-Pognetto et al, 2011) with over twenty different types of interneurons providing domain-specific, functionally distinct GABAergic input onto principal neurons and each other (Klausberger and Somogyi, 2008). Although many molecules and signaling pathways have been identified to regulate hippocampal GABAergic synapse development (Huang and Scheiffele, 2008; Ko et al, 2015; Krueger-Burg et al, 2017; Kuzirian and Paradis, 2011; Lu et al, 2016), a general framework for development of diverse GABAergic synapses has not been identified.…”
Section: Introductionmentioning
confidence: 99%
“…MAGI2 has been implicated in both glutamatergic (Deng et al, 2006) and GABAergic pathways (Sassoe-Pognetto et al, 2011). SNPs of MAGI2 have been associated with performance in the Wisconsin Sorting Card Test (WCST) in patients with SCZ (Koide et al, 2012), whereas in animal models it was shown to modulate long-term memory and associative learning (Emtage et al, 2009;Stetak et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Rather, they are organized around a core scaffolding protein, gephyrin, which forms multimeric complexes by auto-aggregation and by interacting with other postsynaptic proteins, including GABA A receptors (GABA A R), glycine receptors (GlyR), neuroligins (NL), and collybistin (CB) [13]. Models to explain the formation and maintenance of either glycinergic or GABAergic synapses are still fragmentary [14][15][16], notably because the biochemical composition of their PSD is poorly characterized and because gephyrin structure is only partially resolved. The paucity of PDZ domains in proteins forming GABAergic and glycinergic PSDs implies, however, that protein-protein interactions are based largely on other motifs.…”
Section: Introductionmentioning
confidence: 99%